Cytomegalovirus Genotype Distribution Among Congenitally and Postnatally Infected Patients: Association of Particular Glycoprotein (g)B and gN Types With Symptomatic Disease. (7th October 2015) - Brañas, Patricia; Blázquez-Gamero, Daniel; Galindo, Alberto; Prieto, Columbiana; Olabarrieta, Iciar; Cuadrado, Irene; Folgueira, Lola
Abstract: Background.  Human cytomegalovirus is a leading cause of congenital infection, and there are limited data on prognosis markers in disease development. We aimed to study 3 virology targets (glycoprotein [g]B, gN, and UL144) to assess their correlation with congenital infection and various organ system involvement. Methods.  Forty-eight congenital cases and 58 postnatally infected children were included (2003–2014). Genotyping for the 3 targets and distribution among the cohorts were investigated, and the relationship between the gB, gN, and UL144 types with clinical manifestations in congenital infection was also studied. Results.  All of the genotypes were similarly represented among cohorts, and the most prevalent were the UL144B, gB1, and gN1 genotypes. The gB2 genotype was associated with abnormal image findings by ultrasound and/or magnetic resonance in congenital infection (odds ratio [OR], 6.2; 95% confidence interval [CI], 1.1–34.3; P = .036); the gN1 genotype was associated with an elevated risk of developing neurological disorders (OR, 7.0; 95% CI, 1.1–45.9; P = .043). Both gN1 and gB2 were independent factors for symptomatic infection. Statistical analyses showed no association between any UL144 genotype and disease severity. Conclusions.  All of the genotypes can be involved in congenital infection, although the gB2 and gN1 genotypes might be associated with a more serious illness.